PENGARUH PENERAPAN METODE STUDI KASUS DALAM EFEKTIFITAS PEMBELAJARAN - IBRAHIM IBRAHIM (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2023)
This study aims to see how far the effect of applying the case study method is in creating learning effectiveness, especially in the State and Regional Financial Administration courses in semester VI students of the State Administration Study Program, Faculty of Social and Political Sciences, Universitas Pejuang Republic of Indonesia. The effectiveness of learning is measured from several indicators, including student participation in following the learning process starting from timeliness, participation in lectures, participation in discussions, participation in asking questions, participation in responding to answers and responses. With several indicators that serve as a reference in measuring the effectiveness of learning, one method that remains to be used is the application of the case study method. The case study learning method is a method that stimulates students to always think critically in an effort to solve a given case starting from problem formulation, data collection, data management, data analysis to drawing conclusions. With the teaching experience produced in the application of the case study method, students' attention is focused on the learning process which results in learning taking place effectively. And with the learning conditions created like this, it can guarantee the achievement of the learning objectives that have been formulated. ABSTRAKPenelitian ini bertujuan untuk melihat sejauh mana pengaruh penerapan metode studi kasus dalam menciptakan efektifitas pembelajaran khususnya pada mata kuliah Administrasi Keuangan Negara dan Daerah pada mahasiswa semester VI Program Studi Ilmu Administrasi Negara fakultas Ilmu Sosial dan Ilmu Politik Universitas Pejuang Republik Indonesia. Efektifitas pembelajaran diukur dari beberapa indikator antara lain, partisipasi mahasiswa dalam mengikuti proses pembelajaran mulai dari ketepatan waktu, partisipasi dalam perkuliahan, partisipasi dalam diskusi, partisipasi dalam mengajukan pertanyaan, partisipasi dalam merespon jawaban dan tanggapan. Dengan beberapa indikator yang menjadi rujukan dalam mengukur efektifitas pembelajaran maka salah satu metode yang tetap untuk digunakan adalah penerapan metode studi kasus. Metode pembelajaran studi kasus adalah metode yang merangsang siswa untuk selalu berpikir kritis dalam upaya menyelesaikan kasus yang diberikan mulai dari perumusan masalah, pengumpulan data, pengelolaan data, análisis data sampai melahirkan kesimpulan. Dengan pengalaman mengajar yang dihasilkan dalam penerapan metode studi kasus maka siswa perhatiannya terfokus pada proses pembelajaran yang mengakibatkan pembelajaran berlangsung dengan efektif. Dan dengan kondisi pembelajaran yang tercipta seperti ini dapat menjami tercpainya tujuan pembelajaran yang telah dirumuskan.